CTA423 : Drawing for animation 2 / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course is an extension course of Drawing for Animation 1 which emphasizes drawings and sketches on emotions, body posture and gestures, body language, force and gravity, rhythm, volume, exaggeration and facial expression. Drawing activities include life drawing of human figure, animals and still objects in the studio and exterior location namely zoo, parks and streets. This course also stresses on the styles of sketching, line of action, character design and characterisation and spontaneous sketches.